IMPLEMENTATION OF LOAD BALANCING ON WIFI CORNER FOR RT/RW NET SERVER REDUNDANCY - Nurhidayat; Amuharnis (RADJA PUBLIKA, 2026)
As community-based networks increasingly rely on the internet, providing stable, reliable, and uninterrupted service has become essential. However, public internet hubs like